Integrated care to address child and adolescent health in the 21st century: a clinical review - Fazel, M; Townsend, A; Stewart, H; Pao, M; Paz, I; Walker, J; Sawyer, S; Sharpe, M (Wiley, 2021)
Background Increasing specialisation and technical sophistication of medical tools across the 21st century have contributed to dramatic improvements in the life-expectancy of children and adolescents with complex physical health problems. Concurrently, there is growing appreciation within the community of the extent that children and adolescents experience mental disorders, which are more prevalent in those with complex chronic, serious or life-limiting health conditions. In this context, there are compelling reasons for paediatric services to move to a model of care that promotes greater integration of child psychiatry within the medical, somatic teams that care for children and adolescents in children’s hospitals. Aims In this article, we discuss the range of medical disorders managed by contemporary paediatrics. Materials and Methods We conducted a broad review of the literature and existing services, and use individual accounts to illustrate adolescents’ healthcare preferences in the context of the challenges they experience around their mental health. Results Relevant disorders include life-limiting disorders, such as cancer; disorders involving the brain, such as epilepsy; common chronic disorders, such as asthma and diabetes; psychiatric emergencies, such as deliberate self-harm; and conditions that most commonly present to paediatric services, but where psychiatric input is required, such as severe eating disorders, somatic symptom disorders and gender dysphoria. The persisting legacy of the historical separation of physical and mental health services is described. Yet there are many models of service integration that can promote more collaborative care between psychiatrists and medical specialists, including some which have been taken to scale. Discussion In essence, clinical teams in children’s hospitals require more collaborative approaches that facilitate early recognition and treatment of the psychological aspects of illness as an integral part of patient-centred, family-focussed paediatric care, rather than as something that is bolted on when things go wrong. Conclusion Whilst trust and goodwill between services and providers will be required for novel models of care to be implemented, evaluation of these new models and incorporation of young people’s healthcare preferences is needed.